Exploring the oceans - "Hall, Stephen" (Horus Editions: London, 1998)
Presents an introduction to man's knowledge and means of exploring the ocean. Examines the ocean floor, tides, coastlines, mapping the seas, ships, submarines, fishing, scuba diving, shipwrecks, ocean and coastal life, seabirds, coral reefs, ocean pollution, mining the sea and ocean power. Suggested level: primary, intermediate, junior secondary
Keywords: Underwater exploration